A case study of PT pseudosections constructed in the MnNCKFMASH (MnO-Na2O-CaO-K2O-FeO-MgO-Al2O3-SiO2-H2O) system for metapelitic rocks in the garnet zone of the Silgará Formation, southwestern Santander Massif (Colombia): Estudio de caso de seudosecciones PT construidas en el sistema MnNCKFMASH (MnO-Na2O-CaO-K2O-FeO-MgO-Al2O3-SiO2-H2O) para rocas metapelíticas en la zona de granate de la Formación Silgará, en el Macizo de Santander suroccidental (Colombia) (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
PT pseudosections constructed in the MnNCKFMASH (MnO-Na2O-CaO-K2O-FeO-MgO-Al2O3-SiO2-H2O) system based on bulk-rock chemistry and mineral chemistry data of metapelitic rocks in the garnet zone of the Silgará Formation, southwestern Santander Massif (Colombia) were evaluated based on the application of computer programs such as THERIAK/DOMINO, GTB and GIBBS. They can be used to estimate peak metamorphic PT conditions and constrain parts of metamorphic PT paths. The previously published PT conditions (495-518 oC and 4.4-5.5 kbar garnet zone) are confirmed by the resultant pseudosections in in the MnNCKFMASH system with garnet + potassium feldspar + biotite + muscovite + quartz as the stable mineral assemblage. Several mineral reactions, such as chlorite after biotite and garnet, sericite after plagioclase, chlorite+sericite after staurolite, reveal a retrograde metamorphism, and the formation of these hydrous phases probably took place during decompression at lower PT conditions in the presence of high amounts of H2O.